Pesantren Berwawasan Profetik sebagai Agen Moderasi Beragama di Era Globalisasi: Studi Kasus Pesantren Mahasiswa An-Najah Purwokerto - Arauf , Muta Ali (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2022)
This study aims to understand the relation between globalization and religious plurality in a deep understanding. Globalization often creates many problems in human life, one of the problems related to the issue of religious plurality. Sometimes a biased understanding of heterogeneity creates a lot of misunderstandings that lead to attitudes that tend to be intolerant. For this reason, moderation in religious attitude is needed, so that people's perspectives are not trapped in truth claims. One of the effort to raise an understanding of religious moderation is through pesantren. The prophetic form of pesantren, based on prophetic philosophy or prophetic social science, is deemed capable of providing the public with a broad understanding of religious moderation. This study discusses the phenomenon of pesantren with a prophetic perspective which is considered capable of being an agent of religious moderation. This research was conducted at Pesantren Mahasiswa An Najah Purwokerto and the research approach is qualitative. In introducing the spirit of religious moderation, Peseantren An Najah student boarding school made a breakthrough as in the following activities: First, conducting Interfaith dialogue. Second, Grounding the spirit of nationalism. While the most important strategy in efforts to religious moderation is the cultivation of nationalism. Third, Peace Education. As the most basic of the content of religious moderation is peace education.